Matrix protein synthesis by glomerular mesangial cells in culture: Effects of transforming growth factor β (TGFβ) and platelet-derived growth factor (PDGF) on fibronectin and collagen type IV mRNA - Hänsch, Gertrud Maria; Wagner, Christof; Bürger, Antje; Dong, Wenjie; Staehler, Gerd; Stöck, Michael (Journal of cellular physiology, 1995)
The pathogenesis of glomerular scarring is multifactional; recent evidence suggests that transforming growth factor β (TGFβ), a pleiotropic cicatricial mediator, may promote mesangial sclerosis by enhancing the production of extracellular matrix proteins. We studied the effect of TGFβ1 and TFGβ2 on collagen type IV and fibronectin (FN) synthesis in human glomerular mesangial cells in culture (GMC). Two hours after addition of TGFβ, an up to twofold increase in abundance of collagen type IV mRNA was found, which further increased up to fivefold within 24 h. Addition of cycloheximide did not inhibit the TGFβ effect, but caused by itself an up to twofold increase in the abundance of collagen type IV mRNA after 2 h. Together with collagen mRNA, the mRNA for FN and for platelet-derived growth factor (PDGF) was also enhanced. PDGF was found to enhance abundance of the collagen type IV and fibronectin mRNA in GMC. A neutralizing antibody to PDGF or a PDGF-antisense oligonucleotide partly inhibited the TGFβ-induced increase of collagen type IV mRNA, suggesting that TGFβ can affect the collagen type IV synthesis not only directly but also indirectly via the synthesis of PDGF. © 1995 Wiley-Liss, Inc.